2014
DOI: 10.1088/2041-8205/784/1/l7
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Characterization and Detection of Ethyl Mercaptan in Orion

Abstract: New laboratory data of ethyl mercaptan, CH 3 CH 2 SH, in the millimeter and submillimeter-wave domains (up to 880 GHz) provided very precise values of the spectroscopic constants that allowed the detection of gauche-CH 3 CH 2 SH towards -2 -Orion KL. 77 unblended or slightly blended lines plus no missing transitions in the range 80 -280 GHz support this identification. A detection of methyl mercaptan, CH 3 SH, in the spectral survey of Orion KL is reported as well. Our column density results indicate that meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
137
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 33 publications
4
137
0
Order By: Relevance
“…Altogether, we reduced 3000 of unidentified lines through these studies. At this point, we were ready to search for new molecular species, detecting methyl acetate and gauche-ethyl formate ) and gauche-ethyl mercaptan (Kolesniková et al 2014) for the first time in space, and providing the tentative detection of phenol (Kolesniková et al 2013). These new species together with the work of López et al (in prep., about vibrationally excited CH 3 OCOH and CH 3 COOH) account for 1000 lines.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Altogether, we reduced 3000 of unidentified lines through these studies. At this point, we were ready to search for new molecular species, detecting methyl acetate and gauche-ethyl formate ) and gauche-ethyl mercaptan (Kolesniková et al 2014) for the first time in space, and providing the tentative detection of phenol (Kolesniková et al 2013). These new species together with the work of López et al (in prep., about vibrationally excited CH 3 OCOH and CH 3 COOH) account for 1000 lines.…”
Section: Resultsmentioning
confidence: 97%
“…Up to date, we performed a deep analysis of the data (15 papers have been already published): identifying more than 15 000 spectral features (Tercero et al 2010;, detecting new molecules in space (CH 3 COOCH 3 and g-CH 3 CH 2 OCOH in Tercero et al 2013; NH 3 D + in Cernicharo et al 2013; CH 3 CH 2 SH in Kolesniková et al 2014; also tentative detections of c-C 6 H 5 O in Kolesniková et al 2013 and upper limit calculations for the column density of non detected molecules −cis-CH 2 CHCH 2 CN and cis-CH 2 CHCH 2 NC− in Haykal et al 2013b) and several new isotopologues and Table 2. (1…”
Section: Observations Data Reduction and Overall Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CS was the first sulphur bearing molecule detected in the interstellar medium (Penzias et al 1971 Kolesniková et al (2014) in Orion. Previously methyl meracaptan CH3SH was first detected in SgrB2 (Linke et al 1979) followed by observations in the organic-rich hot core G327.3-0.6 (Gibb et al 2000b), and in Orion (Kolesniková et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…About 20 sulfur-containing molecules have been identified in space so far, but only one of them, methyl mercaptan (CH 3 SH), exhibits observable internal rotation splittings (called A-E splittings) because of the internal rotation of the methyl group (Linke et al 1979;Müller et al 2016). Ethyl mercaptan (CH 3 CH 2 SH) has been recently detected in the Orion Cloud (Kolesniková et al 2014), but no A-E splittings could be observed owing to the high barrier to internal rotation.…”
Section: Introductionmentioning
confidence: 99%